2011
DOI: 10.1111/j.1442-200x.2011.03328.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure‐modifying potential of histamine H1 antagonists: A clinical observation

Abstract: Clinical doses of histamine H(1) antagonists have the potential to adversely modify seizures in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…Establishing a diagnosis is often of value even when a clear change in treatment is not indicated by the diagnosis. For example, close and ongoing observation for seizures is now indicated for patient 5 ( TCF4 ), and avoidance of medications that may trigger seizures, such as antihistamines 52. The family can be informed that the disorder is due to a de novo variant, and in the absence of parental mosaicism, other family members are not at risk, and with future pregnancies the recurrence risk for the parents is low.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a diagnosis is often of value even when a clear change in treatment is not indicated by the diagnosis. For example, close and ongoing observation for seizures is now indicated for patient 5 ( TCF4 ), and avoidance of medications that may trigger seizures, such as antihistamines 52. The family can be informed that the disorder is due to a de novo variant, and in the absence of parental mosaicism, other family members are not at risk, and with future pregnancies the recurrence risk for the parents is low.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, children with febrile seizures had lower CSF histamine than those with fever but no convulsions, suggesting an anti-seizure effect of histamine [88,149]. Moreover, it has been found that H1R antagonists increased the incidence of seizures in children [150]. Furthermore, abnormal levels of H1Rs around the focus of epileptic injury in complex partial seizures were noticed in human positron emission tomography studies [151].…”
Section: Epilepsymentioning
confidence: 95%
“…Based on these findings, the suggestion was made that brain histaminergic system may be involved in inhibiting seizures associated with febrile illnesses in childhood (Kiviranta et al, 1995). The clinical data amply documented proconvulsant effects of H 1 R antagonists administered in clinically relevant doses (Churchill and Gammon, 1949; Yokoyama et al, 1993; Takano et al, 2010; Miyata et al, 2011; Zolaly, 2012). Therefore, centrally acting H 1 R antagonists which may increase seizure susceptibility in patients with febrile seizures are neither recommended to these patients nor to PWE.…”
Section: Monoamines In Epilepsy: Preclinical and Clinical Evidencementioning
confidence: 99%